Application of Health Education Based on Phased Transition Theory Model in Continuous Nursing for Patients with Inflammatory Bowel Disease - Hongmei Xiao; Jun Ye (Emergency Medicine International)
Objective. To explore the application effect of health education based on phased transition theory model in the continuous nursing for patients with inflammatory bowel disease (IBD). Method. A total of 106 patients with IBD admitted to the hospital were enrolled as the research objects between October 2020 and September 2021. According to random number table method, they were divided into observation group and control group, 53 cases in each group. The control group was given routine nursing, while observation group was additionally given health education based on phased transition theory model. The nutritional status (serum prealbumin (PA), albumin (ALB), body mass index (BMI)), scores of Disease Knowledge Mastery Scale, exercise of self-care agency scale (ESCA), and Inflammatory Bowel Disease Questionnaire (IBDQ) were compared between the two groups before and after intervention. Results. After intervention, PA, ALB, and BMI in observation group were higher than those in control group (P<0.05), scores of Disease Knowledge Mastery Scale, total mastery rate, scores and total score of ESCA, and scores and total score of IBDQ were significantly higher than those in control group (P<0.05). Conclusion. The application of health education based on phased transformation theory model in the continuous nursing improves disease knowledge mastery, self-care ability, nutritional status, and quality of life in IBD patients.